2023
DOI: 10.3390/nu15081892
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Neutrophil-Percentage-to-Albumin Ratio (NPAR) in Nonalcoholic Fatty Liver Disease and Advanced Liver Fibrosis in Nondiabetic US Adults: Evidence from NHANES 2017–2018

Abstract: Nonalcoholic fatty liver disease (NAFLD) is highly prevalent globally and includes chronic liver diseases ranging from simple steatosis to nonalcoholic steatohepatitis (NASH). The neutrophil-to-albumin ratio (NPAR) is a cost-effective, readily available biomarker of inflammation used to assess cancer and cardiovascular disease prognosis, and it may be of predictive value in NAFLD. This study was to evaluate the associations between the NPAR, the neutrophil-to-lymphocyte ratio (NLR), and the presence of NAFLD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…There was a study has also indicated that FIB-4 ≥ 1.3 results in false positives in 35% of patients ( 42 ). Another study reported an AUC of 0.810 (95% CI: 0.794–0.825) for NPAR in predicting NAFLD, and it was also associated with an increased risk of advanced fibrosis ( 43 ), which seems more superior predictive performance than NAR, as the AUC for NAR in our study was 0.701 (95% CI: 0.694–0.708). However, our study conducted a direct comparative analysis of the predictive capabilities of NAR and NPAR in forecasting NAFLD and NAFLD with liver fibrosis, highlighting the exceptional performance of NAR in these contexts.…”
Section: Discussionsupporting
confidence: 54%
“…There was a study has also indicated that FIB-4 ≥ 1.3 results in false positives in 35% of patients ( 42 ). Another study reported an AUC of 0.810 (95% CI: 0.794–0.825) for NPAR in predicting NAFLD, and it was also associated with an increased risk of advanced fibrosis ( 43 ), which seems more superior predictive performance than NAR, as the AUC for NAR in our study was 0.701 (95% CI: 0.694–0.708). However, our study conducted a direct comparative analysis of the predictive capabilities of NAR and NPAR in forecasting NAFLD and NAFLD with liver fibrosis, highlighting the exceptional performance of NAR in these contexts.…”
Section: Discussionsupporting
confidence: 54%
“…Evaluating the inflammatory and immune landscapes often mandates the quantification of peripheral white blood cells epitomised by lymphocytes in the PNI, a method used inexpensively and widely. A cohort study showed that individuals with NAFLD harbored a higher peripheral blood lymphocyte count than their healthy counterparts, with the obvious significance in statistic [ 43 ]. This observation is consistent with those of multiple clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Still, there are also studies which failed to identify discrepancies in NLR values between subjects with hepatic steatosis and healthy counterparts, but which showed an inverse correlation between neutrophil-percentage-to-albumin ratio (NPAR) and liver attenuation values ( Cucoranu et al, 2023 ). As a matter of fact, NPAR might perform better than NLR in predicting advanced liver fibrosis, in light of the results of a nationwide US study enrolling non-diabetic adults ( Liu and Chien, 2023 ). Moreover, a Turkish study performed on adults proved that NLR does not correlate with severity of fibrosis and of hepatic inflammation, quantified through liver biopsy assessment ( Kara et al, 2015 ).…”
Section: Neutrophil-to-lymphocyte Ratio: a Predictor Of Prognosis And...mentioning
confidence: 99%